POLICY IMPLEMENTATION OF CURRICULUM IN PLURALISTIC MULTICULTURALISM BASED PHILOSOPHY (FALSAFAH) AND RELIGION STUDY PROGRAM AT UNIVERSITAS PARAMADINA - Muhammad Nur Budiyanto; Abdul Hakim; S Sumartono; S Suryadi (Erudio Journal of Educational Innovation, 2020)
Nowadays, religious pluralism (pluralistic multiculturalism) in Indonesia is proliferating. Universitas Paramadina is allegedly a university where Nur Cholis Madjid (Cak Nur) fosters religious pluralism ideology through the curriculum of pluralistic multiculturalism-based philosophy and religious studies programs. This is proven normatively through the curriculum policies in the Philosophy and Religious Studies Programs based on the Decree of the Paramadina Rector Number SKEP-006a/Rek/UPM/I/2008. Those curriculum policies contained the Lecture Program Unit (Syllabus) and the Outline of Teaching Program. They were also allegedly that religious pluralism was taught in one of its courses named the Seminar on Madjid’s Thought. The purpose of this study was to describe and analyze: The implementation of a pluralistic multiculturalism-based philosophy and religious studies program curriculum policy at Universitas Paramadina. The results revealed that the implementation of pluralistic multiculturalism-based philosophy and religious studies programs at Universitas Paramadina used Grindle theory as a grand theory. Normatively, Universitas Paramadina has not been proven to develop, spread, and teach religious pluralism. This means that the policies of the philosophy and religious studies program curriculum are not based on pluralistic multiculturalism but instead based on Islam of the Archipelago. That means a new concept is open, analytical, and critical to building the character of independent thinking in the fields of Islam, Indonesia, and Modernity. Moreover, field data show that Madjid never taught religious pluralism but a plurality. It means the attributes or character of Paramadina’s lecturers and students to understand religious diversity without the belief that all religions are equally true. This is the cause of “misperception” between religious pluralism and plurality for the younger generation/successors (lecturers and students) of Universitas Paramadina. After Madjid died, the younger generation/successor misinterpreted religious pluralism with this plurality, so students did not understand the core meaning of religious pluralism and plurality.